2002
DOI: 10.1002/cncr.10758
|View full text |Cite
|
Sign up to set email alerts
|

Gemcitabine in combination with 5-fluorouracil with or without folinic acid in the treatment of pancreatic cancer

Abstract: Pancreatic cancer is one of the most frequently reported gastrointestinal tumors and has been reported to have a 5-year survival rate of Ͻ 5%. It is most commonly diagnosed at an advanced stage and until recently, the most frequently administered treatment for patients with advanced disease has been palliative 5-fluoro-

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
26
0
1

Year Published

2003
2003
2016
2016

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 40 publications
(27 citation statements)
references
References 32 publications
0
26
0
1
Order By: Relevance
“…The median survival time was 6 weeks longer in the combination arm [17]. The final results of that trial are awaited; however, it should be noted that the addition of 5-FU to gemcitabine [11,18] failed to produce longer survival than with gemcitabine alone in previous randomized trials.…”
Section: Gemcitabine Combinations For Advanced Diseasementioning
confidence: 99%
“…The median survival time was 6 weeks longer in the combination arm [17]. The final results of that trial are awaited; however, it should be noted that the addition of 5-FU to gemcitabine [11,18] failed to produce longer survival than with gemcitabine alone in previous randomized trials.…”
Section: Gemcitabine Combinations For Advanced Diseasementioning
confidence: 99%
“…Chemotherapy has long been considered largely ineffective, but a cautious optimism has recently been expressed since the discovery of new drugs such as gemcitabine (GEM), a fluorinated nucleoside, which used alone or in combination with 5-fluorouracil (5-FU), has been considered effective in terms of antitumour activity and palliation in these patients (Cohen et al, 2002;Heinemann, 2002;Jacobs, 2002;Oettle and Riess, 2002;Evans et al, 2001). Both 5-FU and GEM are fluoropyrimidine prodrugs that need to be converted to cytotoxic metabolites in the tumour cells in order to exert their antitumour activity; several authors have proposed that the two drugs may interact along their respective pathways of activation leading to a synergistic antitumour activity against a number of different malignancies (including pancreatic carcinoma) in vitro and in vivo (Plunkett et al, 1996;Allegra and Grem, 1997;Hidalgo et al, 1997Hidalgo et al, , 1999Berlin et al, 1998 -99;Correale et al, 1999;Schulz et al, 1998;Chu et al, 2001), and for this reason the combination of the two drugs has been investigated in a number of clinical trials in patients with advanced pancreatic carcinoma (Grem, 1996;Hidalgo et al, 1997Hidalgo et al, , 1999Berlin et al, 1998Berlin et al, -99, 2002Cascinu et al, 1999;Correale et al, 2000;Oettle and Riess, 2002).…”
mentioning
confidence: 99%
“…Both 5-FU and GEM are fluoropyrimidine prodrugs that need to be converted to cytotoxic metabolites in the tumour cells in order to exert their antitumour activity; several authors have proposed that the two drugs may interact along their respective pathways of activation leading to a synergistic antitumour activity against a number of different malignancies (including pancreatic carcinoma) in vitro and in vivo (Plunkett et al, 1996;Allegra and Grem, 1997;Hidalgo et al, 1997Hidalgo et al, , 1999Berlin et al, 1998 -99;Correale et al, 1999;Schulz et al, 1998;Chu et al, 2001), and for this reason the combination of the two drugs has been investigated in a number of clinical trials in patients with advanced pancreatic carcinoma (Grem, 1996;Hidalgo et al, 1997Hidalgo et al, , 1999Berlin et al, 1998Berlin et al, -99, 2002Cascinu et al, 1999;Correale et al, 2000;Oettle and Riess, 2002). In previous studies of our groups, we demonstrated that GEM affects 5-FU pharmacodynamics (Correale et al, 1999) and pharmacokinetics, (Correale et al, 2003) and determines synergic antitumour activity in vitro (Correale et al, 1999).…”
mentioning
confidence: 99%
“…It is most commonly diagnosed at an advanced stage and the most frequently administered chemotherapeutic compound for patients with advanced disease has been 5-Fluorouracil (5-FU) [1]. 5-FU alone remains one of the standard treatments in advanced pancreatic cancer.…”
Section: Introductionmentioning
confidence: 99%
“…5-FU alone remains one of the standard treatments in advanced pancreatic cancer. The well-known mechanism of the anti-tumor effects of 5-FU is to inhibit DNA and RNA synthesis [1]. In addition, cell resistance to cytotoxic agents and radiation are two other factors contributing to the poor prognosis of pancreatic cancer [2].…”
mentioning
confidence: 99%